2006
DOI: 10.1007/s10803-006-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Patterns in Youth with Autism Spectrum Disorders

Abstract: The purpose of this study was to examine age-related physical activity patterns in youth with autism spectrum disorders (ASD). Thirty youth, aged 10-19 years, were divided into three groups: elementary (n=9), middle (n=9) and high (n=12) school. Participants wore an accelerometer and completed an activity questionnaire for seven consecutive days. The main findings were that (a) elementary youth are more active than the other groups, regardless type of day or time period, and (b) there are no consistent pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
4
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(166 citation statements)
references
References 29 publications
10
135
4
17
Order By: Relevance
“…For example, sensory sensitivities could lead to a limited diet with poor nutritional value (Kral, Eriksen et al 2013). Lack of accommodation for social and language impairments can create barriers to participating in organized sports and physical activity (Pan and Frey 2006). Poor, restricted diets and lack of exercise are risk factors for obesity, which in turn is associated with increased risk of many major chronic conditions (Guh, Zhang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sensory sensitivities could lead to a limited diet with poor nutritional value (Kral, Eriksen et al 2013). Lack of accommodation for social and language impairments can create barriers to participating in organized sports and physical activity (Pan and Frey 2006). Poor, restricted diets and lack of exercise are risk factors for obesity, which in turn is associated with increased risk of many major chronic conditions (Guh, Zhang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, prerequisite motor skills are necessary to properly perform an activity (Larouche, Boyer, Tremblay, & Longmuir, 2014;Williams et al, 2008); they also increase the likelihood of remaining physically active in the future (Barnett, van Burden, Morgan, Brooks, & Beard, 2009). In a study by MacDonald, Esposito, and Ulrich (2011), the authors found that the physical activity of individuals with ASD decreases with age, which mirrors similar results from previous studies (Pan & Frey, 2006).…”
Section: Dsmsupporting
confidence: 84%
“…Overall, however, evidence suggests that individual with ASD are not likely to engage in high levels of physical activity (Pan & Frey, 2006), and rates are likely to decline as the child ages (MacDonald et al, 2011;Memari et al, 2012). Again, small sample sizes and the ASD population's heterogeneity limit much of the research on ASD.…”
Section: Figure 2: Model Of Contributing Factors For Obesity In Asdmentioning
confidence: 99%
“…Os movimentos repetitivos e estereotipados, falta de interesse, problemas na comunicação e interação social que as crianças com transtorno do espectro apresentam, podem interferir na atividade física (MICACCHI et al,2006). Assim, crianças com TEA estão em maior risco apresentarem um estilo de vida pouco ativo devido aos problemas sociais e comportamentais que caracterizam a sua patologia (PAN; FREY, 2005FREY, , 2006 o que aumenta o risco de várias doenças (LEE et al, 2012) e contribui para a obesidade (PIETILAINEN et al, 2008).…”
Section: Introductionunclassified
“…De fato, diversos estudos têm reforçado a importân-cia da atividade física em indivíduos com TEA, revelando benefícios em diferentes domínios, como, por exemplo, na melhoria da condição física (PETETTI et al, 2007),na redução dos padrões de comportamento mal adaptativo e estereotipados (LANCIONI;O`REILLY, 1998;ELLIOTT et al,1994;YILMAZ et al, 2004), no comportamento agressivo (ALLISON; BASILE; MACDONALD, 1991),e no comportamento anti social (PAN, 2010). Na literatura encontram-se investigados os efeitos de diferentes programas de atividade física em crianças com TEA, nomeadamente programas, que incluem a marcha/caminhada (PETETTI et al,2007;TODD;REID, 2006), a natação (PAN et al, 2006;PAN, 2010;FRAGALA;HALEY;O´NEIL, 2011), a corrida (ROSENTHAL-MALEK; MITCHELL, 1997;PETRUS et al, 2008), e a hipoterapia (BASS; DUCHOWNY; LLABRE, 2009;AJZENMAN;STANDEVEN;SHURTLEFF, 2013;GABRIELS et al, 2012). Independentemente dos tipos/ formas de programas analisados, os resultados parecem convergir e sugerir uma melhoria da proficiência motora com a participação nos programas (WROTNIAK et al, 2006).…”
Section: Introductionunclassified